Sistem Informasi Penjualan dan Persediaan Obat pada Apotek Sejuk Berbasis UI/UX dan Design Thinking - Welmi Simanjuntak; Sri Andayani; Nova Magdalena Br Hombing (Program Studi Informatika Fakultas Ilmu Komputer Universitas Bhayangkara Jakarta Raya, 2026)
Sejuk Pharmacy still faces operational challenges because medicine inventory records and sales transactions are managed manually. This condition leads to stock data discrepancies, reporting delays, and a risk of recording errors. This study aims to design a User Interface (UI) and User Experience (UX) for a sales and medicine inventory information system at Sejuk Pharmacy to improve operational efficiency. The method used is Design Thinking, consisting of the empathize, define, ideate, prototype, and testing stages. The result of this study is a prototype of a pharmacy information system that includes medicine data management, sales transactions (Point of Sale), transaction history, and operational reports. The prototype was designed using Figma with a simple and user-friendly interface. The usability testing results indicate that the proposed interface helps users understand system navigation and facilitates inventory management and sales transaction processes.